Current perspectives in the treatment of childhood lichen planus - Sharad D Mutalik; Vasudha A Belgaumkar; Yashashree D Rasal (Wolters Kluwer Medknow Publications, 2021)
Childhood lichen planus (CLP) is relatively common in India. With a mean age of onset at 7-8 years, CLP poses a therapeutic challenge as most guidelines for treatment cater to adult lichen planus (LP) with no defined evidence-based recommendations for CLP. Each case of CLP needs customized therapy with a step-wise approach. Topical corticosteroids are ably supported by topical calcineurin inhibitors, while oral retinoids, immunosuppressants like cyclosporine, and immunomodulators such as dapsone and narrowband ultraviolet B phototherapy are taking center stage in place of oral corticosteroids as systemic treatment modalities. However, the management of mucosal and appendageal LP requires systemic steroids more often than not. For the present review, we extracted the available data published in the English literature (Google Scholar databases, PubMed, and Medline) using search terms "lichen planus," "treatment," "children," "pediatric," and synthesized documented evidence regarding the risk-benefit profile of each therapeutic modality used in CLP. Undoubtedly, reporting of anecdotal successes, case studies, and conducting randomized controlled trials will help to structure consensus guidelines for the therapeutic conundrum of CLP.